2014
DOI: 10.1007/jhep11(2014)133
|View full text |Cite
|
Sign up to set email alerts
|

Muon anomalous magnetic moment and positron excess at AMS-02 in a gauged horizontal symmetric model

Abstract: Abstract:We studied an extension of the standard model with a fourth generation of fermions to explain the discrepancy in the muon (g−2) and explain the positron excess seen in the AMS-02 experiment. We introduce a gauged SU(2) HV horizontal symmetry between the muon and the 4th generation lepton families. The 4th generation right-handed neutrino is identified as the dark matter with mass ∼ 700 GeV. The dark matter annihilates only to (µ + µ − ) and (ν c µ ν µ ) states via SU(2) HV gauge boson. The SU(2) HV ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…They can thus lead to relevant quantum corrections to leptonic precision observables and generate lepton flavour violating decays of leptons that are extremely suppressed in the SM since they vanish in the limit of massless neutrinos. The (g − 2) µ discrepancy [17,18], recently reinforced by the g − 2 experiment at Fermilab [19][20][21][22], with a tension of 4.2 σ compared to the SM prediction [23], can be explained with a Z boson heavier than the electroweak (EW) scale if it couples flavour violatingly to the second and third lepton generation [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Jhep06(2021)068mentioning
confidence: 99%
“…They can thus lead to relevant quantum corrections to leptonic precision observables and generate lepton flavour violating decays of leptons that are extremely suppressed in the SM since they vanish in the limit of massless neutrinos. The (g − 2) µ discrepancy [17,18], recently reinforced by the g − 2 experiment at Fermilab [19][20][21][22], with a tension of 4.2 σ compared to the SM prediction [23], can be explained with a Z boson heavier than the electroweak (EW) scale if it couples flavour violatingly to the second and third lepton generation [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Jhep06(2021)068mentioning
confidence: 99%
“…We have shown that the same masses and coupling can be used to obtain both the relic abundance of DM and required ∆a µ = 2.8 × 10 −9 within 1σ of the experimental value [3,4]. Another model which can explain AMS-02 and muon (g − 2) has been constructed using a gauged horizontal symmetry [31].…”
Section: Jhep03(2016)062mentioning
confidence: 92%
“…They can thus lead to relevant quantum corrections to leptonic precision observables and generate lepton flavour violating decays of leptons that are extremely suppressed in the SM since they vanish in the limit of massless neutrinos. The (g − 2) µ discrepancy [16,17], recently reinforced by the g − 2 experiment at Fermilab [18][19][20][21], with a tension of 4.2 σ compared to the SM prediction [22], can be explained with a Z boson heavier than the electroweak (EW) scale if it couples flavour violatingly to the second and third lepton generation [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%